Upaya Meningkatkan Kemampuan Motorik Kasar Melalui Permainan Tradisional Egrang Batok Batok Pada Anak Usia Dini 5-6 Tahun di Tk Alam Cugenang - Ai Halimah (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study aims to improve the gross motor skills of children aged 5-6 years through the traditional game of Egrang Batok at Kindergarten Alam Cugenang. Traditional games as the nation's cultural heritage have great potential in stimulating children's development, especially in gross motor aspects. This research is a class action research (PTK) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects in this study were 15 children of group B at Alam Cugenang Kindergarten. Data collection techniques are carried out through observation, interviews, and documentation. The instrument used was an observation sheet for children's gross motor development. Indicators of gross motor ability include the ability to walk on Egrang Batok, maintain body balance, and coordination of footwork. The results of the study showed that children's gross motor skills improved after participating in the Egrang Batok game activities. In pre-action, only 26.6% of children achieved age-appropriate developmental indicators. After the action in the first cycle it increased to 60%, and in the second cycle it reached 86.6%. This improvement shows that the traditional game of Egrang Batok is effective.